Characterization of the Schizosaccharomyces pombe orthologue of the human survival motor neuron (SMN) protein. - Owen, N; Doe, C; Mellor, J; Davies, K (2000)
Childhood onset spinal muscular atrophy (SMA) is a common autosomal recessive disorder primarily characterized by the loss of lower alpha motor neurons. The underlying chromosomal defects causing SMA have been found in the survival motor neuron (SMN) gene. SMN has been shown previously to play a role in both snRNP biogenesis and mRNA processing, although direct evidence for the relationship between SMN and disease pathology has not been elucidated. SMN orthologues have been isolated in many species including Caenorhabditis elegans and Danio rerio. To study the function of SMN, we have identified and characterized the Schizosaccharomyces pombe orthologue of human SMN, smn1 (+). We have demonstrated that smn1 (+) is essential for viability in S.pombe and yeast expressing missense mutations in Smn1p, which mimic mutations in patients with Type I SMA, show significant mislocalization of the protein and a decrease in cell viability. Wild-type Smn1p is localized predominantly in the nucleus whereas yeast expressing Smn1p with missense mutations or deletions of specific domains of the protein accumulate cytoplasmic aggregates. Overexpression of Smn1p results in an increase in the growth rate of cells. Furthermore, mutations within two highly conserved protein interaction domains have a dominant-negative effect on growth, indicating that each domain is of functional significance in S.pombe. These dominant phenotypes can be suppressed by overexpression of murine Smn in the same cell. Given the structural and functional similarities between the protein in fission yeast and higher eukaryotes, S.pombe will be an ideal organism to study the role of SMN in RNA processing.